Bacterial interactions during sequential degradation of cyanobacterial necromass in a sulfidic arctic marine sediment - Albert L. Müller (Department of Microbiology and Ecosystem Science, Centre for Microbiology and Environmental Systems Science, University of Vienna); Claus Pelikan (Department of Microbiology and Ecosystem Science, Centre for Microbiology and Environmental Systems Science, University of Vienna); Julia R. de Rezende (Center for Geomicrobiology, Department of Bioscience, Aarhus University); Kenneth Wasmund (Department of Microbiology and Ecosystem Science, Centre for Microbiology and Environmental Systems Science, University of Vienna); Martina Putz (Department of Microbiology and Ecosystem Science, Centre for Microbiology and Environmental Systems Science, University of Vienna); Clemens Glombitza (NASA Ames Research Center); Kasper U. Kjeldsen (Center for Geomicrobiology, Department of Bioscience, Aarhus University); Bo Barker Jørgensen (Center for Geomicrobiology, Department of Bioscience, Aarhus University); Alexander Loy (Department of Microbiology and Ecosystem Science, Centre for Microbiology and Environmental Systems Science, University of Vienna) (Environmental Microbiology, 2018)
The abstract is available here: https://uscholar.univie.ac.at/o:1005813 The abstract is available here: https://uscholar.univie.ac.at/o:1005813